P28_013 - 13 Let the emf be V Then V = iR = i(R R where i =...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
13. Let the emf be V .Th en V = iR = i 0 ( R + R 0 ), where i =5 . 0A, i 0 =4 . 0A and R 0 =2 . 0Ω
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 11/12/2011 for the course PHYS 2001 taught by Professor Sprunger during the Fall '08 term at LSU.

Ask a homework question - tutors are online